Primary resistance to ALK inhibitors in KLC1/ALK -rearranged pleural metastatic lung adenocarcinoma: a case report - Siblini, Laura; Schott, Roland; Trensz, Philippe; Pencreach, Erwan; Bender, Laura (Translational lung cancer research, 2023)
Anaplastic lymphoma kinase ( ) rearrangement confers sensitivity to second- and third-generation ALK inhibitors, which have become the standard of care for ALK-positive non-small cell lung carcinoma (NSCLC). However, primary resistance to these inhibitors remains a rare and poorly understood phenomenon, especially in cases involving kinesin light chain 1 ( )/ -rearranged metastatic NSCLC. In this report, we present a unique and challenging case of primary resistance to second- and third-generation ALK tyrosine kinase inhibitors (TKIs) attributed to gene fusion partners in a patient with ALK-positive pleural metastatic NSCLC. The patient's disease progression was rapid and unresponsive to multiple lines of ALK-targeted therapies, including alectinib, brigatinib, and lorlatinib, underscoring the need for a deeper understanding of primary resistance mechanisms in such cases. The occurrence of primary resistance to ALK inhibitors in metastatic NSCLC with rearrangement is an infrequent occurrence, and its underlying mechanisms remain elusive. This case emphasizes the importance of further research to elucidate the specific mechanisms of primary resistance to ALK TKIs in non-canonical fusion partners like . Developing targeted therapies for such rare cases is a clinical challenge that warrants continued investigation and innovation in the field of precision oncology.